2016
DOI: 10.1097/dbp.0000000000000303
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Correlates of HIV Disclosure Among Children and Adolescents in Low- and Middle-Income Countries: A Systematic Review

Abstract: ObjectiveDisclosure of HIV status among children and adolescents living with HIV has both beneficial and challenging aspects. To address existing knowledge gaps and update the literature on childhood disclosure, we conducted a systematic review on caregivers’ perceptions and practices of HIV disclosure in low- and middle-income countries (LMICs).MethodsStandard databases were searched for studies conducted in LMICs, published in English between 2004 and 2015. Excluded articles were reviews or case reports, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
96
4
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 74 publications
(119 citation statements)
references
References 37 publications
15
96
4
4
Order By: Relevance
“…The level of disclosure identified in our study was higher compared with previous studies in Ethiopia (17.4% to 39.5%),14 23 24 East Africa (26% to 43.1%),15 28 29 West Africa (21% to 29%),21 30 South Africa 39.6%31 and a review of 22 primary studies in low/middle-income countries (1.7% to 41%)%) 32. The higher level of disclosure in our study may be attributed to the higher mean age of children.…”
Section: Discussioncontrasting
confidence: 87%
See 1 more Smart Citation
“…The level of disclosure identified in our study was higher compared with previous studies in Ethiopia (17.4% to 39.5%),14 23 24 East Africa (26% to 43.1%),15 28 29 West Africa (21% to 29%),21 30 South Africa 39.6%31 and a review of 22 primary studies in low/middle-income countries (1.7% to 41%)%) 32. The higher level of disclosure in our study may be attributed to the higher mean age of children.…”
Section: Discussioncontrasting
confidence: 87%
“…Similar findings have been reported elsewhere 14 24 28. A review article by Britto et al in low/middle-income countries reported deception as high as 49.5% where caregivers provided a non-HIV-related reason for explaining illness and healthcare visits 32. Deception is used by caregivers as a coping mechanism for their lack of self-efficacy to manage disclosure and fear of negative outcomes 24 37 39 40.…”
Section: Discussionsupporting
confidence: 55%
“…The disclosure of diagnosis to children, in particular, has been shown to be dependent on the growing child's cognitive abilities as well as attitudes and goals of the caregiver towards disclosure (Chaudoir, Fisher, & Simoni, 2011). Caregivers' concerns towards non-disclosure stem from its potential negative impact, including fear of negative psychological reactions among the children, and fear of subsequent disclosure to others, leading to stigmatization and further discrimination (Britto et al, 2016; Pinzón-Iregui et al, 2013). However, several clinical reports have indicated positive outcomes associated with disclosure including the promotion of trust, improved adherence, enhanced access to support services, open family communication and better long-term health and emotional well-being in children (Wiener et al, 2007; Lipson, 1994; Funck-Brentano, 1995; Mellins & Brackis-Cott, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Further, we found that parents and caregivers in this study seemed to be quite dependent on medical personnel for the process of disclosure. This may reflect the somewhat more paternalistic role played by medical personnel in some cultural settings (Britto et al, 2016). Future guidelines will need to delve deeper into the specific details of what information would qualify as ‘disclosure’ and address the need for support from medical personnel during the process of disclosure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation